PEMETAAN STATUS HARA NITROGEN PADA LAHAN SAWAH INTENSIF DI KABUPATEN SIGI PROVINSI SULAWESI TENGAH - Munir, Nur Annisa; Rois, Rois; Thaha, Abdul Rahim (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2024)
This study mapped the nitrogen nutrient status in intensive paddy fields in Sigi Regency, Central Sulawesi, using GPS to determine sampling locations. From June to December 2020, soil analysis was conducted at Tadulako University's Soil Science Laboratory. The results showed alarmingly low nitrogen levels across the study area. Specifically, in Palolo Subdistrict, nitrogen levels ranged from 0.01% to 0.08% across 207.1 hectares (91.2% of total paddy land), while in Gumbasa and Sigi Biromaru Subdistricts, levels were similarly low, covering 331.2 and 137.2 hectares, respectively, accounting for 100% of each paddy field.